Histone deacetylases 1 and 2 inhibition suppresses cytokine production and osteoclast bone resorption in vitro. Issue 1 (21st June 2019) - Algate, Kent; Haynes, David; Fitzsimmons, Tracy; Romeo, Ornella; Wagner, Florence; Holson, Edward; Reid, Robert; Fairlie, David; Bartold, Peter; Cantley, Melissa
Abstract: The regulation of epigenetic factors is an emerging therapeutic target of immune function in a variety of osteolytic pathologies. Histone deacetylases (HDAC) modify core histone proteins and transcriptional processes, in addition to nonhistone protein activity. The activated immune response in rheumatoid arthritis, periodontitis, and prosthetic implant particle release stimulates the catabolic activity of osteoclasts. In this study, we investigated the effects of novel therapeutic agents targeting HDAC isozymes (HDAC 1, 2, and 5), previously shown to be upregulated in inflammatory bone disorders, in cytokine‐stimulated human monocytes and osteoclasts in vitro. Inhibiting HDAC 1 and 2 significantly reduced gene expression of IL‐1β, TNF, MCP‐1, and MIP‐1α in TNF‐stimulated monocytes, while suppressing secretions of IL‐1β, IL‐10, INF‐γ, and MCP‐1 ( P  < .05). Osteoclast formation and bone resorption were also significantly diminished with HDAC 1 and 2 inhibition, through reduced NFATc1 expression and osteoclast specific target genes, TRAF6, CTR, TRAP, and Cathepsin K ( P  < .05). Similar trends were observed when inhibiting HDAC 1 and to a lesser extent, HDAC 2, in isolation. However, their combined inhibition had the greatest anti‐inflammatory and antiosteoclastic effects. Targeting HDAC 5 had minimal effects on these processes investigated in this study, whereas a broad acting HDACi, 1179.4b, had widespread suppressive outcomes. This study demonstrates that targeting HDACs is a potent and effective way of regulating the inflammatory and catabolic processes in human monocytes and osteoclasts. It also demonstrates the importance of targeting individual HDACs with an overall aim to improve efficiency and reduce any potential off target effects. Abstract : Epigenetic modulation through targeted histone deacetylase (HDAC) inhibition has recently been identified as an effective method for regulating inflammatory and bone destructive profiles in osteolytic diseases. This study identified the importance of the individual HDAC 1 and HDAC 2 isoform during proinflammatory signaling in monocytes/macrophages and osteoclastic bone resorption, whereby inhibition of these individual HDACs significantly suppresses the inflammatory processes and bone destruction in vitro.